Analisis Kualitas Portal Komik Digital Interaktif Pikolo Dengan Metode Webqual 4.0 - Arifin, Akhmad Dakhilul; Anwariningsih, Sri Huning; Haris, Firdhaus Hari Saputro Al (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2021)
The comic industry in Indonesia is currently in a period of growth after nearly 3 (three) decades of suspended animation. This is due to the lack of innovation in the comic industry, both in terms of facilities and content. The publication of digital comics is currently one solution so that works from comic artists can reach readers. The development of an interactive digital comic publication media application called Portal Inovasi Komik Lokal (PiKOLO) aims to provide an alternative digital comic platform that provides interactive reading features and can be a publication tool for comic artists, especially local comic artists. The PiKOLO application was developed using the Codeigniter framework, with a PHP programming base and a MySQL database. Application testing is carried out using the WebQual 4.0 method. Testing is carried out by distributing questionnaires to comic activists through social networks and comic artists' communities within a predetermined time span. The results of the test show that the PiKOLO application's usability / reusability results in a value of 4.03. As for the aspect of information quality, the average value obtained was 4.06. The service interaction aspect gets an average score of 4.04, and the overall aspect gets an average score of 4.06 from a maximum scale of 5.